Sequence-Directed DNA Curvature in Replication Origins Segments - Fiorini, Adriana; Gimenes, Fabrícia; Neto, Quirino Alves de Lima; Rosado, Fábio Rogério; Fernandez, Maria Aparecida (IntechOpen, 2011)
None